RELATIONSHIP BETWEEN SELF-EFFICIENCY AND DEPRESSION AMONG EDUCATIONAL SCIENCES STUDENTS AT AL-ALBAYT UNIVERSITY - Al-Masaeed, Aslan; Hamadneh, Iyad M. (European Scientific Journal, ESJ, 2015)
The aim of this study is to find out the relationship between selfefficiency and depression among educational sciences students at Al-albayt University, in the light of two variables: academic level and sex. The study was conducted on a sample of 193 students. Data was collected using general self-efficiency scale and Back depression checklist. ANOVA and correlation coefficient were used to find out the relationship between study variables. Results showed a high level of self-efficiency among subjects, as well as a negative relationship between self-efficiency and depression. However, results also showed that there is no statistically significant difference in the respondent’s responses due to their academic level or sex.